Efektivitas Low Density Lipoprotein (LDL) dari Kuning Telur Ayam terhadap Kualitas Semen Cair Domba - Dwitya Citraesti; Wahono Esthi Prasetyaningtyas; Ni Wayan Kurniani Karja (Jurnal Sain Veteriner, 2021)
Low-Density Lipoprotein (LDL) extracted from egg yolk (LDL) has recently known can eliminate the adverse effect associated in the use of fresh egg yolk. The role of LDL in liquid preservation at 4°C of ram sperm has not been explored. This research evaluates the effects of substituting egg yolk with LDL in ram sperm preservation at 4 °C on 5 days. The objective of this research was to assess the effects of substituting egg yolk with LDL for use as an extender in sperm preservation at 4°C, as well as on spermatozoa motility, viability, morphology, plasma membrane, and acrosome integrity, for 5 days. The semen was subsequently divided into five and diluted with Tris–fresh egg yolk (K), Tris–LDL5% (LDL5), Tris–LDL10% (LDL10), Tris–LDL15% (LDL15), and Tris–LDL20% (LDL20). The result showed a significant difference between LDL to fresh egg yolk for ram sperm quality (P<0.05). The effectiveness of LDL on sperm quality decreased following by its concentration. Even though up to 20% concentration of LDL, it can not preserve the quality of diluted semen for motility, viability, and plasm membrane integrity.